Formation and Decomposition of CO2 Intercalated Graphene Oxide - Eigler, Siegfried; Dotzer, Christoph; Hirsch, Andreas; Enzelberger-Heim, Michael; Müller, Paul (Chemistry of Materials, 2012)
The formation, stability, and decomposition of CO intercalated graphene oxide was analyzed by FTIR, TGAMS, TGA-IR, AFM, and SEM for the first time. We found that the formation starts at 50 °C and develops up to 120 °C. The formation process can be best observed by FTIR spectroscopy, and the product is stable at ambient conditions. At higher temperatures, the decomposition of CO intercalated graphene oxide occurs due to the release of water, CO , and CO that can be monitored by TGA-MS and TGA-IR analysis. AFM and SEM images can visualize the formation of blisters in GO films that become instable at 210 °C. We further prepared graphene oxide with a low water-content and found that the formation of CO was significantly suppressed and CO became the major species responsible for the weight loss. In addition we prepared OH treated graphene oxide to elucidate the formation process of CO and found C O O by TGA-MS analysis that proves the crucial role of water during CO formation. From these experiments we propose that hydrate species are key-intermediates for the formation of CO . Hence, it seems likely that rearrangement reactions that can proceed via hydrate intermediates, known from organic chemistry, are probably responsible for the formation of carboxylic acids at the edges of graphene oxide sheets after sonication of graphite oxide. Further, our investigations prove that graphene oxide is less stable than shown by TGA measurements. This has a high impact on the electronic properties of reduced graphene oxide, especially for all those using it for electronic applications. © 2012 American Chemical Society.